Risk Quotient of Airborne Paraquat Exposure among Workers in Palm Oil Plantation - Maksuk Maksuk; Tan Malaka; Suheryanto Suheryanto; Abu Umayah (International Journal of Public Health Science (IJPHS), 2018)
Paraquat is the herbicide widely used at palm oil plantations, although usage it in some countries has been banned and restricted. Paraquat spraying was not appropriate procedure could be polluted the environment and lead to health disorders workers. Paraquat could enter the body through inhalation, dermal and ingestion, one of frequent routes through inhalation during spraying weeds in plantation areas. This study aimed was to analyze potential inhalation dose and Risk Quotient to workers at palm oil plantation. This research was a descriptive study with cross sectional design and analysis of environmental health risk methods. Airborne Paraquat residue was collected from 8 workers with occupational activity as a supervisor and sprayer. Airborne Paraquat residue was measured for 25 minutes during spraying by using personal air sampler at worker’s breathing zone. Airborne Paraquat residue was detected by High Performance Liquid Chromatography (HPLC) with NIOSH 5003 methods. The average of airborne Paraquat residue was 0.0125 mg/m3, it values was less than the Threshold Limit Value (0.05 mg/m3) of American Conference of Government Industrial Hygienists, but the average of potential inhalation dose was 0.001 mg/kg/day for worker’s weight 55 kg, it was value higher than Acceptable Operator Exposure Limit (0.0005 mg/kg/day) and the calculation of Risk Quotient (RQ) was more than 1, it conditions was unacceptable for workers. Although, airborne Paraquat residue were safe, but potential inhalation dose and Risk Quotient (RQ) were unsafe for workers, cause it can be lead to lung function disorders. Therefore, for further studies it was necessary to assess the lung function of workers and the use of personal protective equipment must be completely and standard.